2020
DOI: 10.16910/jemr.12.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Improving eye–computer interaction interface design: Ergonomic investigations of the optimum target size and gaze-triggering dwell time

Abstract: The Midas touch is reflected by the interactive feedback of interface functional elements, and a low level of spatial accuracy is related to the interaction area. This study tried to solve these two problems from the perspective of human-computer interactions and ergonomics. Two experiments were conducted to explore the optimum target size and gaze-triggering dwell time of the eye–computer interaction (ECI) system. Experimental Series 1 was used as the pre-experiment to identify the size that has a greater tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…For example, Paulus and Remijn [31] found that a dwell time of 600 ms was rated easiest by users to select objects. Niu et al [13] found that selecting a button size of 256 × 256 px was more accurate than selecting a button size of 128 × 128 px, whereas Penkar et al [17] identified a circular area of 150 px as being the easiest to select. Feit et al [32] suggested that the shape and size of buttons should be designed individually according to the position of the button on the screen.…”
Section: Background and Related Work 21 Gaze-based Interactions In Hcimentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Paulus and Remijn [31] found that a dwell time of 600 ms was rated easiest by users to select objects. Niu et al [13] found that selecting a button size of 256 × 256 px was more accurate than selecting a button size of 128 × 128 px, whereas Penkar et al [17] identified a circular area of 150 px as being the easiest to select. Feit et al [32] suggested that the shape and size of buttons should be designed individually according to the position of the button on the screen.…”
Section: Background and Related Work 21 Gaze-based Interactions In Hcimentioning
confidence: 99%
“…Second, neuroscience studies have shown that the foveal vision of adults is limited to the central 1.5-2 • of the visual field [43,44]. Third, commonly tested button sizes in previous studies ranged from 3.3 • to 7.7 • (radii of approximately 1.6 • to 3.8 • ) [13,32]. Fourth, points and polylines should be assigned different buffer sizes because they differ geometrically: points are 0-dimensional objects and polylines are 1-dimensional objects with an attribute of length.…”
Section: Parameter Values To Be Testedmentioning
confidence: 99%
See 2 more Smart Citations
“…Eye-Computer-Interaction (ECI) is an interactive method of directly controlling a technological device by means of ocular parameters. In this context, Niu, Gao, Xue, Zhang & Yang ( 8 ) conducted two experiments to explore the optimum target size and gaze-triggering dwell time in ECI. Their results have an exemplary application value for future interface design.…”
mentioning
confidence: 99%